Avians as a Model System of Vascular Development - Bressan, Michael (Methods Mol Biol, 2015)
For more then 2000 years philosophers and scientists have turned to the avian embryo with questions of how life begins (Aristotle; Needham, 1959). Then, as now, the unique accessibility of the embryo both in terms of acquisition of eggs from domesticated fowl, and ease at which the embryo can be visualized by simply opening the shell, have made avians an appealing and powerful model system for the study of development. Thus, as the field of embryology has evolved through observational, comparative, and experimental embryology, into its current iteration as the cellular and molecular biology of development, avians have remained a useful and practical system of study.